COMMUNITY CARE FOR PERSONS WITH SCHIZOPHRENIA IN INDONESIA (Proceedings of the International Conference on Public Health, 2023)
Mental healthcare services for people with mental illness have enhanced healthy family relationships, friendships, and even interaction with colleagues at work for persons receiving the care services. Many factors influence the practice of the mental health profession, including family involvement, social support, and coordinated comprehensive care. This research aimed to explore the role of family and community in the practice of care for people with schizophrenia in Yogyakarta, Indonesia. Methods: This was qualitative research conducted in 2021, with interviews and Focus Group Discussions as data collection methods. The participants included eight family members of individuals with confirmed schizophrenia and members of the local community. The analysis employed an inductive thematic analysis to explore various roles in mental health handling. Results: Kinship patterns, cultural values, and religious practice greatly influence care. Care is generally perceived as an act of assistance to functional limitations. It often becomes an area of negotiation in the family and community, particularly on the issues of finances, roles, and responsibilities, and on how the method of care should be delivered. In some cases, families with their social capital created a care network that enables the community's support system. On the other hand, the community also has a formal and informal social organization to advocate for adequate treatment. Conclusion: Community and family support for persons with schizophrenia is an essential factor for optimal treatment. Nevertheless, there is a need to improve knowledge and awareness of mental health in the community to ensure proper treatment is delivered.
Keywords: Care; Community; Role; Mental Illness